(3v+5)(8+v)=0

Simple and best practice solution for (3v+5)(8+v)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3v+5)(8+v)=0 equation:


Simplifying
(3v + 5)(8 + v) = 0

Reorder the terms:
(5 + 3v)(8 + v) = 0

Multiply (5 + 3v) * (8 + v)
(5(8 + v) + 3v * (8 + v)) = 0
((8 * 5 + v * 5) + 3v * (8 + v)) = 0
((40 + 5v) + 3v * (8 + v)) = 0
(40 + 5v + (8 * 3v + v * 3v)) = 0
(40 + 5v + (24v + 3v2)) = 0

Combine like terms: 5v + 24v = 29v
(40 + 29v + 3v2) = 0

Solving
40 + 29v + 3v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(8 + v)(5 + 3v) = 0

Subproblem 1

Set the factor '(8 + v)' equal to zero and attempt to solve: Simplifying 8 + v = 0 Solving 8 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + v = 0 + -8 Combine like terms: 8 + -8 = 0 0 + v = 0 + -8 v = 0 + -8 Combine like terms: 0 + -8 = -8 v = -8 Simplifying v = -8

Subproblem 2

Set the factor '(5 + 3v)' equal to zero and attempt to solve: Simplifying 5 + 3v = 0 Solving 5 + 3v = 0 Move all terms containing v to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3v = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3v = 0 + -5 3v = 0 + -5 Combine like terms: 0 + -5 = -5 3v = -5 Divide each side by '3'. v = -1.666666667 Simplifying v = -1.666666667

Solution

v = {-8, -1.666666667}

See similar equations:

| 3r-18=3 | | K^2+7x=0 | | -13/5+21/2x=-29/40 | | 25(-8)= | | 2a-6+25=10a | | x+50+x+40+90=180 | | 5r+25=40 | | 6x-7=-2x-9 | | b+10=2b-20 | | bx-a=ac | | 10x=ex-28 | | v^4-13v^3+36v^2=0 | | 15*ln(1+.5x)=ln(2+15x) | | 2(2x+1)=3x-4(1-x) | | 6x+24=6x+12 | | y+y^2+1=14 | | -18(-4)= | | 1.3x-0.28=-2.1 | | 48n-9n^2=36 | | -13+y+y^2=0 | | 0=5x^4-2x^2-4 | | -400.00x+4000=0.00 | | -b+ax=cb | | 3a+5(a-4)= | | -4.5=-.5(x-7.1) | | 10x-23=-123 | | (v^2-13v-36)=0 | | -29+s=-58 | | v^2(v^2-13v-36)=0 | | 4-6p+5p= | | ax-b=cb | | 36=24N-3N^2 |

Equations solver categories